2004
DOI: 10.1192/bjp.184.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Neural response to emotional prosody in schizophrenia and in bipolar affective disorder

Abstract: Patients with schizophrenia and bipolar disorder may display some left-lateralisation of the normal right-lateralised temporal lobe response to emotional prosody.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 27 publications
(37 reference statements)
6
81
1
Order By: Relevance
“…The results of the current study are in line with Mitchell et al (2004), who found atypical low activation in the right hemisphere (i.e., inferior frontal and superior temporal gyri, and amygdala) of BD patients, as compared to healthy controls, while listening to emotional prosody. This finding was interpreted by the authors as a reduced capacity to process emotional prosody in BD patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the current study are in line with Mitchell et al (2004), who found atypical low activation in the right hemisphere (i.e., inferior frontal and superior temporal gyri, and amygdala) of BD patients, as compared to healthy controls, while listening to emotional prosody. This finding was interpreted by the authors as a reduced capacity to process emotional prosody in BD patients.…”
Section: Discussionsupporting
confidence: 92%
“…This finding was interpreted by the authors as a reduced capacity to process emotional prosody in BD patients. However, given that Mitchell et al (2004) did not control for mood state, it was unclear whether atypical functional brain organization, and atypical right hemispheric functioning in particular, only occurs during manic/depressive mood states or also applies to euthymic states in BD patients.…”
Section: Discussionmentioning
confidence: 99%
“…One preliminary study by Mitchell and colleagues 78 compared the neural responses of controls and patients with schizophrenia and bipolar disorder to recorded scenarios presented in happy, sad and neutral intonations. Patients were scanned while passively listening to affective prosody stimuli and while actively attending to the emotional intonation of each phrase.…”
Section: Neuroimaging Studies Of Affective Prosody Recognition In Patmentioning
confidence: 99%
“…Several of the regions in this subnetwork deserve further consideration. For example, prior functional neuroimaging studies in BD have found evidence of superior temporal gyrus dysfunction during emotional processing [223,258,259] as well as during rest [237,260]. Medial temporal structures in particular (such as the amygdala and hippocampus, which constitute components of our sub-network) have been implicated in the structural pathology of BD patients and unaffected relatives, though findings have been inconsistent [261].…”
Section: Discussionmentioning
confidence: 99%
“…Bipolar disorder (BD) is a relatively common and highly disabling condition [30,223], the etiological and pathophysiological underpinnings of which are poorly understood. The characteristic profile of depressive and manic episodes in BD likely reflect impaired functioning of the neural substrates of emotion regulation and cognitive control.…”
Section: Introductionmentioning
confidence: 99%